2021
DOI: 10.1016/j.injury.2021.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Distal femur fractures have a higher mortality rate compared to hip fractures among the elderly: Insights from the National Trauma Data Bank

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…From January 10, 2015, to December 2019, there were more than 31,000 patients in the Medicare claims data who sustained an operatively managed distal femur fracture who met inclusion criteria. Most of the patients (90%, 28,251/ 31,380) received fixation with either ORIF (22,917) or IMN (5,334) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From January 10, 2015, to December 2019, there were more than 31,000 patients in the Medicare claims data who sustained an operatively managed distal femur fracture who met inclusion criteria. Most of the patients (90%, 28,251/ 31,380) received fixation with either ORIF (22,917) or IMN (5,334) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is intuitive that patients with geriatric distal femur fracture and patients with geriatric hip fracture have similar mortality rates. Tsai et al 22 recently reported significantly greater in-hospital mortality in geriatric distal femur fractures as compared with geriatric hip fractures. This study is the largest study on geriatric distal femur fractures in the literature, and the overall 1-year mortality of 22.5% is similar to several previous studies ranging from 13% to 38%.…”
Section: Discussionmentioning
confidence: 99%
“…Adults above the age of 49 had osteopenia or osteoporosis at rates of 22.4% and 47.9%, respectively [ 11 ]. Another study also indicated that distal femoral fracture was associated with higher mortality rates, as determined by a retrospective analysis after adjusting for potential factors [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mortality more than 8 days after ambulance transport or after transfer to other institutions was not able to be obtained and included. Meanwhile, Tsai et al [25] reported an in-hospital mortality rate of 6.7% within an average of 6.65 days of hospitalization. Some differences in patient demographics and data collection methods existed between the work by Tsai et al [25] and our study.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Tsai et al [25] reported an in-hospital mortality rate of 6.7% within an average of 6.65 days of hospitalization. Some differences in patient demographics and data collection methods existed between the work by Tsai et al [25] and our study. Their data were collected from the United States National Trauma Data Bank registry, and data collection was limited to relatively severe patients over 65 years old with some kind of comorbid illness or secondary fractures due to high-energy trauma.…”
Section: Discussionmentioning
confidence: 99%